Diagnostic Value of the Combination of Golgi Protein 73 and Alpha-Fetoprotein in Hepatocellular Carcinoma: A Meta-Analysis. - Meiyu Dai; Xiaoli Chen; Xuexiang Liu; Zheng Peng; Jie Meng; Shengming Dai (PLoS ONE, 2015)
Conflicting results have been widely reported on the use of Golgi protein 73 (GP73) as a serum biomarker for diagnosing hepatocellular carcinoma (HCC). This study evaluated the accuracy of GP73, alpha-fetoprotein (AFP), and GP73 + AFP for diagnosing HCC. The meta-analysis was performed on 11 studies that were selected by means of a comprehensive systematic literature review. Summary diagnostic accuracy, meta-regression analysis for heterogeneity and publication bias, and other statistical analyses were performed using Meta-Disc (version 1.4) and Stata (version 12.0). Pooled sensitivity, specificity, and diagnostic odds ratio were 0.77 (95% CI: 0.75-0.79), 0.91 (95% CI: 0.90-0.92), and 12.49 (95% CI: 4.91-31.79) for GP73; 0.62 (95% CI: 0.60-0.64), 0.84 (95% CI: 0.83-0.85), and 11.61 (95% CI: 8.02-16.81) for AFP; and 0.87 (95% CI: 0.85-0.89), 0.85 (95% CI: 0.84-0.86), and 30.63 (95% CI: 18.10-51.84) for GP73 + AFP. The area under the curve values were 0.86, 0.84, and 0.91 for GP73, AFP, and GP73 + AFP, respectively. These results indicate that for HCC diagnosis, the accuracy of GP73 was higher than that of AFP, and that GP73 + AFP exhibited significantly higher diagnostic accuracy than did GP73 or AFP alone.